2014
DOI: 10.1063/1.4900772
|View full text |Cite
|
Sign up to set email alerts
|

Communication: On the stability of ice 0, ice i, and Ih

Abstract: Using ab initio methods, we examine the stability of ice 0, a recently proposed tetragonal form of ice implicated in the homogeneous freezing of water [J. Russo, F. Romano, and H. Tanaka, Nat. Mater. 13, 670 (2014)]. Vibrational frequencies are computed across the complete Brillouin Zone using Density Functional Theory (DFT), to confirm mechanical stability and quantify the free energy of ice 0 relative to ice I h . The robustness of this result is tested via dispersion corrected semi-local and hybrid DFT, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 51 publications
0
29
0
1
Order By: Relevance
“…[209], where a novel metastable phase was identified, called Ice 0, with a tetragonal unit cell with 12 molecules, whose thermodynamic and structural properties are intermediate between the melt and the solid crystalline phase. The thermodynamic stability of the new phase was originally demonstrated for mW and TIP4P/2005 models of water [209], and additional density functional calculations have confirmed that, among the known metastable ice phases, Ice 0 has the closest free energy to that of stable ice I [240,241].…”
Section: Local Structural Ordering and Homogeneous Crystal Nucleationmentioning
confidence: 99%
“…[209], where a novel metastable phase was identified, called Ice 0, with a tetragonal unit cell with 12 molecules, whose thermodynamic and structural properties are intermediate between the melt and the solid crystalline phase. The thermodynamic stability of the new phase was originally demonstrated for mW and TIP4P/2005 models of water [209], and additional density functional calculations have confirmed that, among the known metastable ice phases, Ice 0 has the closest free energy to that of stable ice I [240,241].…”
Section: Local Structural Ordering and Homogeneous Crystal Nucleationmentioning
confidence: 99%
“…28 Both DMC and LRDMC provide excellent benchmark values for weakly interacting systems, as established in a number of studies. [29][30][31][32][33][34][35][36]39,58,59 We used here a standard setup, described in detail in the Supporting Information. The stochastic error associated with the QMC evaluations of the adsorption energy is ca.…”
Section: Qmc Calculationsmentioning
confidence: 99%
“…120 The Jas- been assessed in previous studies. [29][30][31][32][33][34][35][36]39,58,59 This choice of the complex-minus-far method is explained by two considerations: (i) DMC calculations (as well as any many-body electronic structure method) are affected by size-effects due to the periodicity of the system that are much larger that those of DFT, and they are sizeable also in the big supercells considered here; complex-minus-fragments method is instead much more affected by the finite time-step bias, so it would require a τ that is at least one order of magnitude smaller.…”
Section: S1 Dmc Setupmentioning
confidence: 99%
“…The recent theoretical studies of water freezing stated the emergence of ferroelectric ice named ice 0, which may be formed only from supercooled water, followed by formation of ice Ih or Ic [18,19]. This process may take place, according to the cited studies, at temperatures below −23 • C. Previously the rise of ε s at the temperature below −37 • C was discovered for water in silicate material MCM-41 with cylindrical pores [36] at low frequencies of the order of 10 Hz.…”
Section: Discussion Of Resultsmentioning
confidence: 99%